Analysis of Liquefaction Potential in Sungai Limau District Padang Pariaman Regency Using the Multichannel Analysis of Surface Wave (MASW) Method - Angeline Chika Rorensia; - Syafriani; - Hamdi; - Akmam; Letmi Dwiridal (PILLAR OF PHYSICS, 2023)
Sungai Limau is one of the sub-districts in Padang Pariaman Regency which was badly damaged by the earthquake on 30 September 2009. Geologically, the Sungai Limau area is included in the category of cambisol soil types in the form of layers of sand, making it vulnerable to liquefaction due to earthquakes. This research was conducted to analyze the liquefaction potential using the Multichannel Analysis of Surface Wave (MASW) method. The MASW method can produce 2D Vs profiles to describe the structure and types of rock-forming materials at each depth and layer. This method can detect underground surfaces Vs to a depth of 30 meters. Data collection was conducted at Sungai Limau using the sysmatrack-MAE tool with 4 observation tracks. Each measurement uses a distance between geophones of 4 meters. The Vs results from MASW will be compared with the classification of soil types from UBC 1997. The average results of the shear wave velocity at a depth of 30 m (Vs30) in this study are 322.9 m/s for the first track, 303 m/s for the second track, 311 m /s for the third and fourth track. The four tracks fall into the same classification, namely medium soil type (class D). The results of the liquefaction potential analysis using the MASW method show that the first line has a high level of liquefaction potential in the third layer with a value of Vs 337 m/s (class D). The second track has a high level of liquefaction potential in the third layer with a value of Vs 314 m/s (class D). The third track has a fairly high level of liquefaction potential in the second layer with a value of Vs 209 m/s (class D). The fourth track has a high level of liquefaction potential in the second layer with a value of Vs 198 m/s (class D). The fourth and fifth layers on the entire track have no liquefaction potential with Vs ranging from 400-550 m/s (Class C).